Strategic design management capability framework for small and medium Bumiputera furniture manufacturers through evaluation of industry indicators - Osman, Nur Syazana (2019)
The importance of design management capability is to enhance the design performance of Bumiputera furniture SME sector which has gradually diversified with the expansion of the meaning and influences of design. Design is now regarded as a critical strategic tool to increase a commercial competitiveness in order to sustain in a complex global market. Concurrently, the importance of embracing the extensive design management capability including product innovation, organizational architecture, and operational process in furniture manufacturing has been identified by industry players and the government as a way to increase the performance of an organization. As highlighted, this research is looking at the issue of declining Bumiputera manufacturers participation in the export market compared to domestic market. Therefore, the research aims to create a strategic design management capability framework as a comprehensive overview of Bumiputera furniture SME manufacturers to further improve the design performance towards nine industry indicators evaluation. This study also provided an ‘Action Process’ and strategic matrix as a tool to lead the Bumiputera manufacturers in order to achieve successful product commercialization. In this research, the integration of quantitative and qualitative as mixed methods are used in addressing the research questions. The questionnaire survey was conducted face-to-face to obtain higher return rate. Apart from that, this study also uses in-depth interview to have a deeper understanding regarding this field. Additionally, the framework is assessed by the industry key players comprising manufacturing and design experts through focus group discussion and survey with prospective model of design management capabilities and recommended implementation processes. Through the analysis of the literature and interviews, the twenty-three design capability characteristics were selected to provide a comprehensive reliable list of characteristics inclusive of applicability, benefit and implementation, which directly and indirectly influence the three comprehensive areas in Bumiputera furniture SME; (i) creative thinking innovation, (ii) knowledge expertise, and (iii) IP management and manufacturing performance. In order to achieve successful transition as ODM/OBM manufacturers, it requires Bumiputera manufacturers to take an effective strategy through; (i) product creation development, (ii) integrated talent management, and (iii) protecting ownership and commercial production. In doing so, the recommended framework could be used as a comparative guide to evaluate design performance and help the manufacturers achieve their organizational goals.